Bamboo charcoal as electrode material for vanadium redox flow batteries - Schilling, Monja; Ershov, Alexey; Debastiani, Rafaela; Duan, Kangjun; Köble, Kerstin; Scherer, Simon; Lan, Linghan; Rampf, Alexander; Faragó, Tomáš; Zuber, Marcus; Cecilia, Angelica; Liu, Shaojun; et al. (Energy Advances, 2024)
Large-scale energy storage is becoming more critical since the share of energy from renewable sources has increased steadily in recent years. Vanadium redox flow batteries (VRFBs) are a promising candidate for such applications. However, this technique still needs to overcome challenges to enhance battery efficiency, and the investigation of new electrode materials is crucial in this process. In this study, we evaluate bamboo charcoal (BC) as an electrode material for VRFBs for the first time. Bamboo is a rapidly growing renewable carbon source and is thermally treated for use in electrochemical applications. The structure, wettability, wetting behavior, and electrochemical performance of differently-doped BC electrodes are investigated in detail. Scanning electron microscopy and X-ray micro- and nano-computed tomography show the promising channel structure of BC, beneficial for the electrolyte transport through the electrode. Additionally, synchrotron-based time-resolved X-ray radiography and micro tomography was used for an in situ study of the electrolyte flow through the BC channels. These investigations and the dynamic vapor sorption measurements prove that the aqueous electrolyte wets the material easily. Furthermore, we studied the electrochemical performance using cyclic voltammetry and electrochemical impedance spectroscopy combined with the distribution of relaxation times analysis. The undoped BC turned out to have a high catalytic activity towards the vanadium redox reaction, whereas the N-doped BC exhibits improved wettability. In conclusion, BC has great potential to be a suitable and renewable VRFB electrode material.
CRIS-Team Scopus Importer:2024-05-31